1983
DOI: 10.1080/09553008314550991
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Radiation-induced Skin Tumours in Mice and Variations with Dose Rate

Abstract: Mice were exposed to weakly penetrating beta-particles from an external source, using 12 different surface doses ranging from 5.4 to 260 Gy and given at four different dose rates from 200 to 1.7 cGy/min. As in previous investigations, both epidermal and dermal tumours occurred with the latter predominating. The lowest surface dose to produce a statistically significant increase in skin tumours was 21.7 Gy, no effect being detected with doses of 5.4-16.3 Gy. The dose-response curves rose steeply when obvious in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…However, in the experiments of Coggle and Williams (1990), no reduction in effectiveness was found over a 1000-fold range of -radiation doses down to 0.1 Gy min À1 . In contrast, Hulse et al (1983) did find a reduction from a total of 30 tumours to five in comparable numbers of mice when the dose rate was reduced from 1.1-2.0 Gy min À1 to 0.017-0.024 Gy min À1 . Neither the dose rate nor the total dose was low in terms of radiological protection or carcinogenesis in the experiments of Hulse et al (1983) and Williams et al (1986).…”
Section: F33 Sex Rolementioning
confidence: 61%
See 3 more Smart Citations
“…However, in the experiments of Coggle and Williams (1990), no reduction in effectiveness was found over a 1000-fold range of -radiation doses down to 0.1 Gy min À1 . In contrast, Hulse et al (1983) did find a reduction from a total of 30 tumours to five in comparable numbers of mice when the dose rate was reduced from 1.1-2.0 Gy min À1 to 0.017-0.024 Gy min À1 . Neither the dose rate nor the total dose was low in terms of radiological protection or carcinogenesis in the experiments of Hulse et al (1983) and Williams et al (1986).…”
Section: F33 Sex Rolementioning
confidence: 61%
“…In contrast, Hulse et al (1983) did find a reduction from a total of 30 tumours to five in comparable numbers of mice when the dose rate was reduced from 1.1-2.0 Gy min À1 to 0.017-0.024 Gy min À1 . Neither the dose rate nor the total dose was low in terms of radiological protection or carcinogenesis in the experiments of Hulse et al (1983) and Williams et al (1986). Thus, it is possible, as the experiments of Hulse et al (1983) suggested, that with very low dose rates, say 0.01 Gy day À1 , the reduction in effectiveness may be considerable.…”
Section: F33 Sex Rolementioning
confidence: 61%
See 2 more Smart Citations
“…Albert et al (180) showed that the rat skin tumor yield after grid and sieve nonuniform radiation exposure was markedly delayed compared with uniform exposure. Hulse and colleagues (181)(182)(183) irradiated CBA mice with thallium-204 (204T1) particles using 12 different surface doses (5.4-260 Gy) and 4 different dose rates (1.7-200 cGy/min). The average latent period for tumor formation was 7 months, and more than 70% of the tumors were of dermal origin, 30% epidermal, and more than 60% were malignant.…”
Section: Carcinogenesismentioning
confidence: 99%